Earth's Fury: The Science of Natural Disasters - Gates, Alexander (Hoboken: Wiley Blackwell, 2022)
Earth$1 (Bs Fury: The Science of Natural Disasters attempts to combine the best features of a scientific textbook and an encyclopedia. It retains the organization of a textbook and adopts the highly illustrative graphics of some of the newer and more effective textbooks. The book$1 (Bs unique approach is evident in its plethora of case studies: short, self-contained and well-illustrated stories of specific natural disasters that are highly engaging for both science and non-science majors. The stories incorporate the science into the event so students appreciate and remember it as part of the story. By relating the event to the impact on society and human lives, the science is placed in the context of the student$1 (Bs real life.s
Includes Index
Keywords: Natural disasters; Hazardous natural phenomena; Geophysics; Disasters$1 (BEnvironmental aspectss; Earth sciences